A cobalt arylphosphonate MOF - superior stability, sorption and magnetism - Zorlu, Yunus; Erbahar, Dogan; Cetinkaya, Ahmet; Bulut, Aysun; Erkal, Turan S.; Yazaydin, A. Ozgur; Beckmann, Jens; Yucesan, Gundog (ROYAL SOC CHEMISTRY, 2019)
We report a novel metal-organic framework (MOF) based on a cobalt arylphosphonate, namely, [Co-2(H-4-MTPPA)]center dot 3NMP center dot H2O (1.3NM center dot H2O), which was prepared solvothermically from the tetrahedral linker tetraphenylmethane tetrakis-4-phosphonic acid (H-8-MTPPA) and CoSO4 center dot 7H(2)O in N-methyl-2-pyrrolidone (NMP). Compound 1 has the highest porosity (BET surface area of 1034m(2) g(-1)) ever reported for a MOF based on an aryl phosphonic acid linker. The indigo blue crystals of 1.3NMP center dot H2O are composed of edge-shared eight-membered Co2P2O4 rings, and are thermally very stable up to 500 degrees C.
Keywords: TETRAPHOSPHONIC ACIDS; METAL; ORGANOPHOSPHONATE; FRAMEWORKS; ZIRCONIUM; AREAS; Chemistry